Carlos Edmundo de Ory and his inclusion in the classic author’s canon. An (im)possible love (Ogigia. Revista Electrónica de Estudios Hispánicos, 2017)
This paper is focused on studying the literary work of the Spanish writer Carlos Edmundo de Ory among the perspective of the literary canon through the point of view from the different critics who brought into this issue throughout points such as, the influences theory, the revisionism or it presence in time. Taking into account Carlos Edmundo de Ory`s volume Diario (1944 – 2010) as a biographical framework, we land into the expression suprafluences(suprafluencias) created to describe the literary, artistic and thoughts influences set by the author. The results evince the need to settle this prolific writer straight to the canon of the classic authors.
Keywords: Carlos Edmundo de Ory; canon; influences; suprafluences